Reactions to (the absence of) control and workplace arrangements: experimental evidence from the internet and the laboratory - Katrin Schmelz; Anthony Ziegelmeyer (Experimental Economics, 2020)
This paper reports an experiment designed to assess the influence of workplace arrangements on the reactions to (the absence of) control. We compare behavior in an Internet and a laboratory principal-agent game where the principal can control the agent by implementing a minimum effort requirement. Then the agent chooses an effort costly to her but beneficial to the principal. Our design captures meaningful differences between working from home and working at the office arrangements. Online subjects enjoy greater anonymity than lab subjects, they interact in a less constrained environment than the laboratory, and there is a larger physically-oriented social distance between them. Control is significantly more effective online than in the laboratory. Positive reactions to the principal's choice not to control are observed in both treatments, but they are significantly weaker online than in the laboratory. Principals often choose the highest control level, which maximizes their earnings.
Keywords: C81; C90; C93; M52; 330; Hidden benefits of abstaining from control; Laboratory; Internet; Workplace arrangements